AB0183 The Effect of Geography on the Efficacy of Sifalimumab, an Anti-Interferon-Alpha Monoclonal Antibody, in Moderate to Severe Systemic Lupus Erythematosus. (9th June 2015) - Khamashta, M.; Illei, G.; Drappa, J.; Wang, L.; Greth, W.
Abstract : Background: The efficacy and safety of sifalimumab were assessed in a Phase IIb, randomized, double-blind, placebo-controlled study of adults with moderate to severe systemic lupus erythematosus (SLE). Sifalimumab is 1 of 2 compounds targeting the type I interferon pathway that is currently under assessment for evaluation in Phase III studies. Objectives: To assess geographic differences as potential confounders of efficacy in a worldwide sifalimumab Phase IIb study. Methods: 431 patients were randomized and received monthly intravenous sifalimumab (200 mg, 600 mg, or 1200 mg) or placebo. The primary efficacy endpoint was the percentage of patients achieving an SLE responder index [SRI] at Week 52. Overall results from this study were presented at the 2014 American College of Rheumatology (ACR) annual meeting. 1 Here we present results from a pre-specified randomization stratification factor based on geographic region: Region 1: high expected response to standard of care (SOC) - Central America, South America, Eastern Europe, Asia; Region 2: low expected SOC response - North America, Western Europe, South Africa. Results: Of the 431 patients, 296 (68.7%) were from Region 1 and 135 (31.3%) from Region 2. Compared with placebo, more patients who received sifalimumab met the primary endpoint (placebo, 45.4%; 200 mg, 58.3%; 600 mg, 56.5%; 1200 mg, 59.8%) with greater response rates observed in Region 1 than in Region 2. There was a larger distinction (Δ) between sifalimumab plus SOC and placebo plus SOC responses in Region 2 compared with Region 1. (Figure ). This distinction was not attributable to differences in baseline SLE Disease Activity Index 2000 (SLEDAI-2K), physician global assessment, or British Isles Lupus Assessment Group (BILAG)-2004 scores which were similar for patients in both regions. Differences in several demographic and clinical characteristics were seen between patients in Region 1 vs Region 2: mean weight (64.7 kg vs 72.8 kg), mean age (38.0 years vs 42.5 years), median time from diagnosis to randomization (80.1 months vs 138.4 months), mean Systemic Lupus International Collaborating Clinics (SLICC)/ACR Damage Index (0.5 vs 1.1), and SOC (use of antimalarials [70.9% vs 78.5%], azathioprine [30.4% vs 15.6%], methotrexate [11.8% vs 21.5%], mycophenolate [3.7% vs 22.2%], and corticosteroids [92.9% vs 68.9%], as well as average corticosteroid dosage [11.7 mg/day vs 9.3 mg/day]). Conclusions: Response to treatment with sifalimumab in adult patients with moderate to severe SLE showed a greater distinction in the SRI endpoint in patients who received sifalimumab vs placebo in Region 2 compared with Region 1. This may, in part, be reflective of regional populations with different baseline characteristics or differences in SOC. References: Khamashta M et al. Arthritis Rheumatol. 2014;66:S10 (Abstract L4) Acknowledgements: Funded: MedImmune. Editorial Assistance: Mark Hughes, PhD, QXV Communications, UK Disclosure of Interest: M. Khamashta Grant/research support from: Bayer, Consultant for: INOVA diagnostics, Medimmune, GSK, UCB, G. Illei Shareholder of: AstraZeneca, Employee of: MedImmune, J. Drappa Employee of: MedImmune, L. Wang Employee of: MedImmune, W. Greth Shareholder of: AstraZeneca, Employee of: MedImmune/AstraZeneca